A Critique on the Book The Quran and Hadith’s Manifestation in Persian Poetry - Zeinab Rezapour (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
This study aims at evaluating the textbook The Quran and Hadith’s Manifestation in Persian Poetry that was published by the Organization for Researching and Composing of University textbooks in the Humanities (SAMT). In comparison with similar works, this textbook has gone a further step and the writer has created a more methodical, comprehensive and applied book. The logical order in expressing discussions, a more comprehensive classification of effectiveness methods along with useful explanations for its examples, and also clear translations from the Quran verses and Hadiths are among the strengths of this book. However, according to the criteria for evaluating textbooks, there are some serious loopholes about this book in terms of form, structure and content that create some problems for students in their learning process and remembering the materials. Failing to refer and cite reliable references in defining the terms, ambiguity, generalization, paradox, the plurality of titles, lack of correspondence with the purposes and the approved educational curriculum, lack of desirable and effective preface, necessity to take updated criteria into account, no benefit and comprehensiveness in compiling the materials along with some weaknesses in form and structure are some of the points which need to be revised and modified in this book.